Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1021/bi00367a074
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of europium(III) with phospholipid vesicles as monitored by laser-excited europium(III) luminescence

Abstract: The technique of laser-excited Eu(III) luminescence was applied to monitor Eu(III) binding to a variety of phospholipids. Eu(III) excitation spectra were similar with and without the presence of neutral phospholipids, while acidic phospholipids changed the spectrum in a concentration-dependent manner. Eu(III) appears to bind to the phosphate moiety with at least a 2:1 phospholipid:metal ion stoichiometry. Analysis of luminescence lifetimes reveals that only one or two waters of hydration are removed from Eu(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…So far, spectroscopy experiments have revealed that metal cations specifically interact with negatively charged moieties of the lipid headgroups [212][213][214][215]. These experiments, together with theoretical simulations [216], have led to an idea that individual ions may interact with multiple headgroups to form complex "lipid-ion networks".…”
Section: Direct Imaging Of Lipid-ion Networkmentioning
confidence: 99%
“…So far, spectroscopy experiments have revealed that metal cations specifically interact with negatively charged moieties of the lipid headgroups [212][213][214][215]. These experiments, together with theoretical simulations [216], have led to an idea that individual ions may interact with multiple headgroups to form complex "lipid-ion networks".…”
Section: Direct Imaging Of Lipid-ion Networkmentioning
confidence: 99%
“…To date, spectroscopy experiments have revealed that metal cations specifically interact with negatively charged moieties of the lipid headgroups. [40][41][42][43] These experiments, together with theoretical simulations, 44) support the idea that individual ions may interact with multiple headgroups to form complex "lipid-ion networks." This concept has been used to explain the previously observed effects of the ions, such as the enhancement of the mechanical strength of membranes 45) and the reduction of the mobility of the lipid molecules therein.…”
Section: Lipid-ion Networkmentioning
confidence: 66%
“…2, the phosphate monoester 1, diester 2, and triester 3 may be formed in monolayers prepared according to the above procedure. While all three compounds can be expected to bind Ca 2 and the other cations used in this study, binding strengths are expected to increase in the order of 3 < 2 < 1 [17]. No attempt to determine the molecular ratios of 1, 2, and 3 on the electrode was made.…”
Section: Sensor Preparationmentioning
confidence: 99%
“…Indeed, it has been shown that cation binding to phosphate esters at phospholipid membrane interfaces is accompanied by partial dehydration of the cation and the phosphate groups [17,21,22]. Therefore, it appears reasonable to explain the weaker responses to the more hydrophilic dications by the energetically unfavorable partial dehydration that is required for the formation of interfacial complexes of these ions.…”
Section: Selectivitymentioning
confidence: 99%
See 1 more Smart Citation